THE ANALYSIS OF CODE SWITCHING AND CODE MIXING USED BY INDONESIAN YOUTUBERS - Sistajati, Ida Ayu Agung Putri; Suputra, Putu Eka Dambayana (Universitas Pendidikan Ganesha, 2022)
This study aimed at analyzing the types of code-switching and code-mixing that were used by the top 5 YouTubers in Indonesia. The design of this research was a descriptive qualitative study since it focused on a single case of the phenomenon of code-switching and code-mixing. Moreover, the data were collected through observing the YouTube videos by the top 5 YouTubers in Indonesia. It was found that there were 482 utterances categorized into code-switching and code-mixing. The type of code-switching used by Indonesian Youtubers included inter-sententially code-switching (98 utterances or 59.4%), intra-sententially code-switching (44 utterances or 26.7%), and emblematic code-switching (23 utterances or 13.9%). While the type of code-mixing included inter-sententially code-mixing (201 utterances or 63.4%) and intra-sententially code-mixing (116 utterances or 36.6%). The most frequently appearing type of code-switching in this study was inter-sententially code-switching. While the type of code-mixing was inter-sententially code-mixing. The result of this study can be the reference in the linguistics and communication field and as the supporting materials in English teaching and learning.